Cooperative and antagonistic contributions of two heterochromatin proteins to transcriptional regulation of the Drosophila sex determination decision. - Li, H.; Rodriguez, J.; Yoo, Y.; Shareef, M.M.; Badugu, R.; Horabin, J.I.; Kellum, R. (PLoS Genetics, 2011)
Eukaryotic nuclei contain regions of differentially staining chromatin (heterochromatin), which remain condensed throughout the cell cycle and are largely transcriptionally silent. RNAi knockdown of the highly conserved heterochromatin protein HP1 in Drosophila was previously shown to preferentially reduce male viability. Here we report a similar phenotype for the telomeric partner of HP1, HOAP, and roles for both proteins in regulating the Drosophila sex determination pathway. Specifically, these proteins regulate the critical decision in this pathway, firing of the establishment promoter of the masterswitch gene, Sex-lethal (Sxl). Female-specific activation of this promoter, Sxl(Pe), is essential to females, as it provides SXL protein to initiate the productive female-specific splicing of later Sxl transcripts, which are transcribed from the maintenance promoter (Sxl(Pm)) in both sexes. HOAP mutants show inappropriate Sxl(Pe) firing in males and the concomitant inappropriate splicing of Sxl(Pm)-derived transcripts, while females show premature firing of Sxl(Pe). HP1 mutants, by contrast, display Sxl(Pm) splicing defects in both sexes. Chromatin immunoprecipitation assays show both proteins are associated with Sxl(Pe) sequences. In embryos from HP1 mutant mothers and Sxl mutant fathers, female viability and RNA polymerase II recruitment to Sxl(Pe) are severely compromised. Our genetic and biochemical assays indicate a repressing activity for HOAP and both activating and repressing roles for HP1 at Sxl(Pe).